Pernikahan Paksa Gadis Dibawah Umur oleh Wali Perspektif Ulama dan Keempat Madzhab - Mohamad Faisal Aulia; Amin Mukrimun (Universitas Islam Negeri Raden Fatah Palembang, 2022)
Abstract: Marriage is one of the themes that gets great attention in Islam because it involves the goals in one of Al-Dharuriyyat Al-Khomsah in Maqashid Al-Shari'ah, namely Hifzh Al-Nasl (keeping offspring). To obtain an accurate and relevant data to the problem under study, the authors use a normative legal research methodology with a library research approach that uses library materials. The results of the discussion show that some scholars are of the opinion that girls are still small and immature so that they cannot make a decision, so in the context of the benefit of the Shari'a it is permissible to marry them; that the girl who has not been able to make a decision then the guardians who have full power to marry her for the benefit of herself based on the rules of the Shari'a in order to avoid damage. The second opinion says that it is not permissible to force a girl to get married, but to wait until she is an adult and her permission can be asked for marriage.